Evaluation of Computed Tomography Guided Fine Needle Aspiration Cytology of Lung Mass with Histological Correlation - Haldar, Ganesh Chandra; Saibal, Md Arif Akbar; Das, Ruhini Kumar; Gupta, Joydev Dutta; Karmakar, Pijush; Dash, Uma (Eastern Medical College Journal, 2022)
Background: Lung cancer is the major cause of cancer related deaths all over the world. CT guided FNAC of lung mass is an effective modality to diagnose lung cancer. Objective: Aim of our study was to evaluate the pathological spectrum of diseases in the lesions of the lung through CT guided FNAC. Materials and Methods: This prospective study was carried out in Eastern Medical College Hospital and a specialized diagnostic center in Cumilla, Bangladesh. Fifty-three (53) patients were selected by convenience sampling. After informed consent CT guided lung FNACs were performed during period of 1 year from July 2021 to June 2022 and cytological diagnoses were made. Reported results and relevant data were recorded in the data sheet and then analyzed by standard statistical method. Results: Total number of cases was 53 and adequate samples were obtained in 100% cases. Among the adequate samples 39 (73.58%) were malignant and 14 (26.42%) were benign or nonmalignant lesions. Among the benign lesions, pulmonary TB cases were most common (8 cases, 57.14%) followed by lung abscess (2 cases, 14.29%). Adenocarcinoma (18 cases, 46.15%) was the most common type of bronchogenic carcinoma followed by squamous cell carcinoma (17 cases, 43.59%), small cell carcinoma (3 cases, 7.69%), NHL (1 case, 2.56%). In male cases, squamous cell carcinoma (41.03%) was the most common type of bronchogenic carcinoma, followed by adenocarcinoma (30.77%). In female cases, adenocarcinoma was the most common type (15 cases, 38%) of bronchogenic carcinoma, followed by squamous cell carcinoma (2 cases, 56%). Conclusion: FNAC is a safe method for the evaluation of lung mass and nodules, and it enables sub-classification of bronchogenic carcinoma in most cases. It is also useful for the diagnosis of tuberculous pulmonary nodules. Eastern Med Coll J. Jan 2023; 8 (1) 24-27